Image Compression Study using Diversified Approaches - Pansare, Jayshree R.; Jadhav, Ketki R (European Journal of Applied Sciences, 2017)
Image compression plays an important role in minimizing irrelevance and redundancy of digital images for efficient transmission and storage. It saves large storage capacity and transmission bandwidth. The aim of image compression algorithm is to reduce amount of data required to represent image with less degradation without loss. This paper studies diversified approaches for compression of images such as FELICS, Wavelet transformation based approach, Prediction based approach, Combination of method based approach and Block coding based approach etc. Under different approaches there are different techniques for compression of image and gives better results than previous state-of-art techniques. Different methods gives different compression ratio, saves memory, and gives high performance. They have their own strength and weaknesses.